2022
DOI: 10.1007/s44197-022-00048-2
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia cepacia Infections at Sites Other than the Respiratory Tract: A Large Case Series from a Tertiary Referral Hospital in Lebanon

Abstract: Objectives The Burkholderia cepacia complex (Bcc), which was originally thought to be a single species, represents a group of 24 distinct species that are often resistant to multiple antibiotics, and usually known to cause life-threatening pulmonary infections in cystic fibrosis patients. Herein we describe a series of non-respiratory Bcc infections, the risk factors and epidemiologic factors, in addition to the clinical course. Patients and methods This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…Most of these bacteria isolated from blood cultures come from patients who have a background of end stage renal disease. This is in accordance with previous study demonstrated that B. cepacia were the most commonly found in blood specimens accounting for which was associated with bloodstream infections ( 15 , 16 ). Moreover, other investigators highlighted the prevalence of B. cepacia detected in 30 patients with bloodstream infections during two-year period ( 17 ) indicating B. cepacia as emerging pathogens in blood stream infections.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Most of these bacteria isolated from blood cultures come from patients who have a background of end stage renal disease. This is in accordance with previous study demonstrated that B. cepacia were the most commonly found in blood specimens accounting for which was associated with bloodstream infections ( 15 , 16 ). Moreover, other investigators highlighted the prevalence of B. cepacia detected in 30 patients with bloodstream infections during two-year period ( 17 ) indicating B. cepacia as emerging pathogens in blood stream infections.…”
Section: Discussionsupporting
confidence: 94%
“…In this investigation, men were more likely to be infected with B. cepacia than women. This is consistent with previous research showing that men are more susceptible to these infections than women ( 14 , 15 , 21 ). It is believed that this may be due to the role of genetic and hormonal factors, i.e.…”
Section: Discussionsupporting
confidence: 93%
“…BCC is primarily recognized for the ability to cause infections in individuals with cystic fibrosis [ 1 , 4 , 11 ], chronic granulomatous disease [ 11 ], and compromised immune systems [ 1 ]. There are increasing reports of BCC infections among patients without cystic fibrosis [ 12 , 13 ] or presenting with clinical symptoms beyond the respiratory system [ 14 ]. However, characteristics such as pregnancy, thalassemia, and eclampsia have not been reported in association with BCC infections.…”
Section: Discussionmentioning
confidence: 99%
“…B. cepacia was identified as the most common cause of early neonatal sepsis in Yemen [ 7 ]. A study conducted in a tertiary hospital in Lebanon reported that BCC infections were more common in refugees [ 8 ]. These findings raise the concern that countries at war might be at increased risk for such infections.…”
Section: Discussionmentioning
confidence: 99%
“…In neonates, BCC infections are usually reported as outbreaks in the neonatal intensive care unit (NICU). In addition to nosocomial infections, very few studies in the literature show that BCC is an important infectious agent group that can also cause community-acquired infections in areas with limited access to healthcare [ 7 , 8 ]. In this study, neonates referred to a NICU in Turkey from different centers, including the cross-border regions of Syria, shortly after birth and who were diagnosed with BCC bacteremia at admission were examined.…”
Section: Introductionmentioning
confidence: 99%